Expression of miR-4739 in Gastric cancer and its Relationship with Clinical Pathological Features of Patients - Wei, Jiaxing; Li, Jun; Geng, Dong; Peng, Yiling; Yang, Bin; Wu, Huixian; Zhou, Yun (Frontiers in Surgery, 2022)
Objective To investigate the expression level of miR-4739 in gastric cancer (GC), analyze its diagnostic value in GC and the relationship with clinical pathological characteristics, and analyze its impact on the prognosis of patients. Methods A total of 96 patients with GC who underwent radical gastrectomy in our hospital from March 2017 to June 2021 were selected. GC tissues from all patients were collected, and normal tissues adjacent to cancer were collected as controls. The expression level of miR-4739 in tissues was detected, the relationship between miR-4739 and different pathological features was analyzed, and the diagnostic value of miR-4739 in GC was analyzed. All patients were followed up after the operation, and the survival time of the patients was set as from the day of the first operation to 1 d when the patients died or the follow-up ended. Results The relative expression level of miR-4739 in the GC tissue was (0.39 ± 0.06), lower than that in the paracancerous tissue (1.18 ± 0.19) (P < 0.05). The AUC of miR-4739 in the diagnosis of GC was 0.705. When the Youden index was 0.320 and the optimal cutoff value was 0.37, the sensitivity was 95.30% and the specificity was 36.70%. The expression level of miR-4739 in our patient was related to the differentiation degree, lymph node metastasis, tumor diameter, and TNM stage (P < 0.05). During the follow-up period, 26 of 96 patients died, and the survival rate was 72.92% (26/96). The median survival time was 29 months in the miR-4739 LE group, which was shorter than 39 months in the miR-4739 HE group (P < 0.05). Univariate analysis showed that age, degree of differentiation, lymph node metastasis, tumor diameter, TNM staging, and miR-4739 expression were all related to the prognosis of the patient (P < 0.05). Multivariate analysis showed that differentiation degree, lymph node metastasis, tumor diameter, TNM staging, and miR-4739 expression were all independent factors affecting the prognosis of the patients (P < 0.05). Conclusion The expression of miR-4739 in GC tissue was down-regulated, and its level was related to the degree of differentiation, lymph node metastasis, tumor diameter, and TNM stage. The expression level of miR-4739 has certain diagnostic value for patients with GC, and the prognosis of patients in LE group was worse than that in HE group.